INTEGRATION OF MACROALGAE IN FISH FARMING: A SUSTAINABLE APPROACH - Flores, Gabriel da Silva Nepomuceno; Dumith, Michelle Torres; dos Santos, Alejandra Filippo Gonzalez Neves (Seven Editora, 2026)
Aquaculture has grown globally due to limitations in extractive fishing and the increasing demand for fish; however, intensive systems generate significant environmental impacts, especially due to nutrient accumulation and deterioration of water quality. The aim of this study was to conduct a meta-analysis of bibliographic data related to research on integrated fish and macroalgae farming systems, highlighting the strategic relevance of the topic in the international scenario and its emerging importance in the Brazilian Aquaculture context. Thirteen studies were selected, totaling 27 valid comparisons. The analysis, performed using multilevel models with lnRR as the effect size, revealed that farming with macroalgae significantly increased fish growth (lnRR = 0.1492; p = 0.0184), corresponding to an average increase of 16.1% compared to monoculture.The heterogeneity among the studies was significant, although partially explained by the evaluated moderators. Among the macroalgae species studied, Gracilaria sp. stood out with the most pronounced positive effect (p = 0.0025), while the duration of the experiments did not significantly influence the results. The absence of publication bias reinforces the reliability of the estimates obtained. In general, the findings show that integrated systems with macroalgae contribute to improving water quality, especially by reducing total ammoniacal nitrogen (TAN) and other nitrogenous compounds, while also favoring fish growth (SGR), based on a systematic review that selected 13 studies, totaling 27 valid comparisons. The analysis, performed using multilevel models with lnRR as the effect size, revealed that the present favors fish growth and increases the environmental and productive sustainability of fish farming. Despite these benefits, there is still a scarcity of studies, especially in tank systems and recirculating aquaculture systems (RAS), indicating the need for further, more standardized, and long-term research to consolidate the mechanisms involved and strengthen the ecological and economic potential of this approach.DOI: https://doi.org/10.56238/sevened2026.008-077